Values-Based Foundation for a U.S. Single Payer Health System Model - Markowitz, Walter; McLeod-Sordjan, Renee (Frontiers in Sociology, 2021)
A universal, single payer model for the American health system aligns with and should emanate from commonly held values contained within the country’s foundational religious teachings, morals, ethics and democratic heritage. The Affordable Care Act in its attempt to create expanded health access has met with significant challenges. The conservative Supreme Court decreases the likelihood of a federal mandated single payer model. As uncertainty of the structure of the healthcare system increases, this paper supports its transformation to a single payer model. Healthcare should be considered a duty within the framework of a Kantian approach to ethics and a social good. Evidently ignoring this duty, the American health system perpetuates a healthcare underclass, with underserved portions of the population, with unequal access to quality care and persistent health status and outcome disparities. The COVID-19 pandemic demonstrated the effect of social determinants on optimal health outcome. A health insurance system based on the nation’s commonly held values has the potential to eliminate these disparities.